You need to multiply both sides by `z - 1` such that:

`(z-1)(z^4+z^3+z^2+z+1) = 0*(z-1)`

You need to convert the product to the left side into a difference of powers such that:

`z^5 - 1 = 0 => z^5 = 1 => z^5 = root(5)1 => z = 1`

**Since the graph below representing the function `f(x)=x^4+x^3+x^2+x+1` , does not intercept x axis, hence, the equation has no real roots but 4 complex roots.**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now